(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article the stylistic role of compound sentences joined asyndentically in poetic works of V. Simonenko is investigated. Certainly, that asyndetic constructions have large expressive possibilities. They strengthen the rhythm of text, create a stylistic syntactic figure - asindeton, which (depending on the structurally-semantic type of suggestion) can be the mean of poetic gradation, vivid parallelism or antitheses.